2014
DOI: 10.1128/aem.04036-13
|View full text |Cite
|
Sign up to set email alerts
|

New In Situ Capture Quantitative (Real-Time) Reverse Transcription-PCR Method as an Alternative Approach for Determining Inactivation of Tulane Virus

Abstract: We found that the ISC-qRT-PCR method could be used to evaluate virus inactivation deriving from damage to the capsid and study interactions between the capsid and viral receptor. Heat, chlorine, and ethanol treatment primarily affect the capsid structure, which in turns affects the ability of the capsid to bind to viral receptors. Inactivation of the virus by these methods could be reflected by the ISCqRT-PCR method and confirmed by TCID 50 assay. However, the loss of the infectivity caused by damage to the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
(26 reference statements)
0
24
0
Order By: Relevance
“…For example, Hirneisen and Kniel (8) found PGM binding to correlate well with plaque assay results for murine norovirus exposed to different heat treatments. Another study utilizing PGM binding for Tulane virus exposed to ethanol, chlorine, and heat showed reductions similar to those observed by 50% tissue culture infective dose determination (10). When PGM was used to evaluate the inactivation of GI.1 Norwalk virus by high-pressure processing, reductions corresponded to those observed in a human feeding study with the same virus (11, 12).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, Hirneisen and Kniel (8) found PGM binding to correlate well with plaque assay results for murine norovirus exposed to different heat treatments. Another study utilizing PGM binding for Tulane virus exposed to ethanol, chlorine, and heat showed reductions similar to those observed by 50% tissue culture infective dose determination (10). When PGM was used to evaluate the inactivation of GI.1 Norwalk virus by high-pressure processing, reductions corresponded to those observed in a human feeding study with the same virus (11, 12).…”
Section: Discussionmentioning
confidence: 68%
“…One method that is widely used is viral receptor binding, most commonly done with histo-blood group antigens (HBGAs). HBGA (or porcine gastric mucin [PGM], which contains some HBGAs) binding has performed well in comparison with the plaque assay when murine norovirus and Tulane virus surrogates were subjected to a variety of physical and chemical stresses (810). In the most compelling work yet, GI.1 Norwalk virus inactivation estimated by a combined PGM binding RT-qPCR method compared favorably to results from a parallel human challenge study evaluating the efficacy of high-pressure processing on norovirus in oysters (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study used an in situ capture qRT-PCR to determine the inactivation of TV and found that this method reflected inactivation of the virus by chlorine or ethanol treatment but not UV irradiation (34). The UV irradiation used in that study did not reduce the ability of TV to bind to its receptor, and subsequent PCR was still able to amplify the target fragment, even though the genome was damaged by UV irradiation and the virus was not able to replicate, as indicated by the results of a cell culture-based assay (34). Taken together, the effectiveness of using a binding method followed by PCR to distinguish between infectious and inactivated viruses might depend on the binding agents and processing methods.…”
Section: Discussionmentioning
confidence: 99%
“…PGM- or synthetic HBGAs- conjugated magnetic beads have been then utilized as a method for concentrating HuNoVs (Tian et al, 2005, 2008; Cannon and Vinjé, 2008) and to estimate the inactivation status of HuNoVs treated by high-pressure processing (HPP) or heat inactivation (Dancho et al, 2012). We further improved the method by coating hybrid binding/PCR reaction containers with PGM to sequester HBGA-binding viruses, which was then followed by in situ amplification of the captured viral genomes by RT-qPCR (Wang and Tian, 2014; Wang et al, 2014). The cultivable Tulane Virus (TV) was used to validate this In Situ Capture RT-qPCR (ISC-RT-qPCR) method (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We further improved the method by coating hybrid binding/PCR reaction containers with PGM to sequester HBGA-binding viruses, which was then followed by in situ amplification of the captured viral genomes by RT-qPCR (Wang and Tian, 2014; Wang et al, 2014). The cultivable Tulane Virus (TV) was used to validate this In Situ Capture RT-qPCR (ISC-RT-qPCR) method (Wang et al, 2014). Our previous work indicated that this method could be used for evaluating inactivation status of TV and HuNoV caused by heat and chlorine treatments (Wang and Tian, 2014; Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%